2001
DOI: 10.1001/archpsyc.58.3.289
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Brain Magnetic Resonance Imaging in Girls With Attention-Deficit/Hyperactivity Disorder

Abstract: Background: Anatomic studies of boys with attentiondeficit/hyperactivity disorder (ADHD) have detected decreased volumes in total and frontal brain, basal ganglia, and cerebellar vermis. We tested these findings in a sample of girls with ADHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
208
2
13

Year Published

2002
2002
2011
2011

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 379 publications
(242 citation statements)
references
References 64 publications
19
208
2
13
Order By: Relevance
“…Boys with ADHD have smaller cerebellum and vermis posterior inferior lobes (lobules VIII-X) compared to healthy controls (Berquin et al, 1998). Posterior inferior cerebellar vermis also is smaller in girls with ADHD compared to healthy controls (Castellanos et al, 2001). As 5 out of 16 subjects in the bipolar group had a comorbid diagnosis of ADHD, this could be a significant confounding variable for this study.…”
Section: Discussionmentioning
confidence: 89%
“…Boys with ADHD have smaller cerebellum and vermis posterior inferior lobes (lobules VIII-X) compared to healthy controls (Berquin et al, 1998). Posterior inferior cerebellar vermis also is smaller in girls with ADHD compared to healthy controls (Castellanos et al, 2001). As 5 out of 16 subjects in the bipolar group had a comorbid diagnosis of ADHD, this could be a significant confounding variable for this study.…”
Section: Discussionmentioning
confidence: 89%
“…Fourth, no girls were tested because we wanted to minimize the differences between groups concerning factors other than diagnosis, though this limits the generalization of our findings to girls with ADHD and their non-affected sisters. It appears, though, that similar deficits in visuo-spatial working memory, inhibition and oculomotor control might be expected in girls with ADHD, since comparable brain abnormalities (Castellanos et al 2001), comparable patterns of familial transmission (Faraone et al 2000) and comparable deficits on a memory-guided saccade task (Castellanos et al 2000) have been observed in girls with ADHD compared to boys with ADHD. Furthermore, even though it has been observed that girls may suffer less from executive deficits than boys (Seidman Familial deficits in memory-guided saccades in ADHD et al 1997) which might also translate in less severe deficits on a memory-guided saccade task, gender differences for executive deficits are not a consistent finding (Seidman et al 2005).…”
Section: Limitationsmentioning
confidence: 84%
“…Furthermore, functional imaging studies have indicated that autistic children have decreased cerebellar activations during a task that requires them to focus attention (73). In addition, cerebellar abnormalities observed with structural MR imaging have also been observed in children suffering from attention deficit hyperactivity disorder (ADHD) (74). Therefore, cerebellar abnormalities may not be specific to schizophrenia.…”
Section: Evidence For Cerebellar Abnormalities In Schizophreniamentioning
confidence: 99%